(untitled) (Journal of Bangladesh Academy of Sciences, 2009)
The paper is concerned with the molar flux of oxygen in the capillary blood when oxygen diffuses from blood to tissue fluid at the middle section of the capillary bed where blood pressure and osmotic pressure of blood are equal. The result shows that the molar flux decreases exponentially with the radius of the capillary. Moreover, it is found that the molar flux increases linearly with the increasing of radial diffusion of oxygen. doi: 10.3329/jbas.v32i2.2429 Journal of Bangladesh Academy of Sciences Vol.32(2) 2008 226-233